(3JShjb NOeGJ GdQYGjI GdESJTaGFjI hGdWHjIs - (3aQjO Jhajb(B, (3fUjQGJs ((3YeGf(B:s (3OGQ GdeSjQI(B,s, 2014)
(3GdGJLGgGJ hGdhGbY GdJShjbj aj eSJTajGJ GdbWGY GdNGU aj GdCQOf, GdedGeM GdYGeI ddUfGYI GdESJTaGFjI aj GdCQOf h NUhUjI GdUMI h GdNOeI GdUMjI, GSJYeGdjI GdNOeGJ GdUMjI h GdESJTaGFjI, GdJNWjW h GdJShjb GdESJQGJjLj ddQYGjI GdESJTaGFjI, GdNOeI GdESJTaGFjI, GdefJL h SYQ GdNOeI GdESJTaGFjI , GdYhV, GdhUhd ddNOeI h SghdI efGdgG , GdJQhjL, GdEJLGgGJ GdeSJbHdjI dEfJGL h JbOje GdNOeGJ GdESJTaGFjI (B.s
Keywords: (3GdGOGQIs; (3GdJShjbs; (3GdNOeGJ GdUMjIs; (3GdQYGjI GdWHjIs